Labor Rights and Confrontation Policies against British Unionism: 1979-90. - Arruda, Pedro Fassoni (Pontifícia Universidade Católica de São Paulo, 2007)
The relations between Margaret Thatcher’s government and unions were tense. The stagflation of the end of 1970’s motivated a change of attitude of the Tories, who broke the social consensus of he postwar period and initiated a counter- offensive in order to weaken unions and eliminate rights that had been conquered in the last century and half. The return of the Tories to power in 1979 was the beginning of a battle of capital aiming at the reduction of the social and political power of unions, strengthened during the previous Labour governments. The hostility of the power bloc toward unions was sufficiently evident when Thatcher declared them “public enemy number one” of the nation, identifying them as the main obstacles to the implementation of neoliberalism and the project of modernization of the State.